F. et Cs. avagy A’ Reményhez és A’ Pillangóhoz Fazekas-módra - Hovánszki, Mária (Studia Litteraria, 2020)
In the article I demonstrate the connection between Fazekas and Csokonai through two poems. Fazekas’s Az érzékenységek énekben (The Senses in Song) was written in imitation of Csokonai’s A’ Reményhez, and A serdűlő bajuszhoz (To the Pubescent Moustache) was written similarly after Csokonai’s A’ Pillangóhoz, in these two poems by Fazekas Csokonai’s influence can be observed from formal characteristics through themes to intertextuality. However, this influence is not merely a copy of form, but it is an expression of Fazekas’s poetic irony and his polemic mentality with Csokonai. Both poems target the Lilla-affection and the love cult of sensitive poetry, as opposed to which, as poetic banter, Fazekas depicts on the one hand, an ordinary woman character who requites love, and on the other hand, a woman of easy virtue. The subtle irony is present on multiple levels in both poems due to the verbunkos (a Hungarian dance originated in military recruiting) and sensibility-classical melody.